Pentahelix Stakeholder Analysis in Developing Ecotourism Based on Paradisaea minor jobiensis Conservation in Sawendui, Yapen Islands - Arlini Cita, Finitya; Basuni, Sambas; Rachmawati, Eva (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Sawendui Village, Yapen Islands Regency, has ecotourism potential Paradisaea minor jobiensis. One approach to preserving P. minor jobiensis is the development of ecotourism. Ecotourism development requires pentahelix stakeholder involvement, which consists of the community, businessmen, government, academics, and media, who have different roles, interests, and influences in terms of ecotourism. The objectives of this study were identify stakeholders, measure the level of interest and influence of stakeholders, and classify stakeholders related to P. minor jobiensis-based ecotourism in Sawendui Village. This study identified 16 stakeholders related to ecotourism using pentahelix grouping, qualitative and quantitative methods through data collection using questionnaires and semi-structured interviews. The Snowball Method was used to get respondents from each stakeholder group. Further study classified stakeholders based on their interests and influence as a pentahelix group. The research results showed that not all ecotourism stakeholders have high interest and influence. The community has the highest interest because they get many benefits from ecotourism, while the government has the highest influence because of its strong institutions. The community is included in the subject classification, the government is included in the key player classification, the media is a context setter, and the crowd consists of academics and businessmen. Increasing stakeholder interest and influence is needed to accelerate ecotourism development. Collaboration between stakeholders in ecotourism needs to be carried out. As a key player, the government has the authority to mobilize all stakeholder groups.